Heteroleptic Cu(ii)–polypyridyl complexes as photonucleases12. (24th May 2016) - Singh, V.; Sharma, K.; Shankar, B.; Awasthi, S. K.; Gupta, R. D.
Abstract : Four new copper(ii )–polypyridyl complexes having tail groups with increasing aromaticity, hydrophobicity and planarity are synthesized. These complexes are found to be avid DNA binders and show efficient nuclease activity under either chemical stimulus or UV-A light irradiation. Abstract : A series of heteroleptic Cu(ii )–polypyridyl complexes with terpyridine (3N)/imidazole (2N) backbones and appended with pyridyl, 2-naphthyl, 9-anthryl and 1-pyrenyl groups are synthesized and evaluated for their photonuclease activity. An array of techniques viz. UV-vis, fluorescence, circular dichroism and thermal denaturation established strong DNA binding affinity ( K b = ∼10 4 –10 6 M −1 ) and the binding modes were correlated with molecular docking studies. Photonuclease efficiency exceeded 90% for all the complexes under identical conditions. Interestingly, DNA binding propensity and photonuclease efficiency followed the increasing size, planarity, aromaticity, π-Stacking ability and hydrophobicity of the peripheral moiety.